Low Vitamin D Levels and Frailty Status in Older Adults: A Systematic Review and Meta-Analysis - Marcos-Pérez, Diego (2020)
Serum vitamin D deficiency is widespread among older adults and is a potential modifiable risk factor for frailty. Moreover, frailty has been suggested as an intermediate step in the association between low levels of vitamin D and mortality. Hence, we conducted a systematic review of the literature and meta-analysis to test the possible association of low concentrations of serum 25-hydroxyvitamin D (25(OH)D), a marker of vitamin D status, with frailty in later life. We reviewed cross-sectional or longitudinal studies evaluating populations of older adults and identifying frailty by a currently validated scale. Meta-analyses were restricted to cross-sectional data from studies using Fried’s phenotype to identify frailty. Twenty-six studies were considered in the qualitative synthesis, and thirteen studies were included in the meta-analyses. Quantitative analyses showed significant differences in the comparisons of frail (standardized mean difference (SMD)—1.31, 95% confidence interval (CI) (−2.47, −0.15), p = 0.0271) and pre-frail (SMD—0.79, 95% CI (−1.58, −0.003), p = 0.0491) subjects vs. non-frail subjects. Sensitivity analyses reduced heterogeneity, resulting in a smaller but still highly significant between-groups difference. Results obtained indicate that lower 25(OH)D levels are significantly associated with increasing frailty severity. Future challenges include interventional studies testing the possible benefits of vitamin D supplementation in older adults to prevent/palliate frailty and its associated outcomes.